2010
DOI: 10.1007/s11240-010-9702-z
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of transformed plants from hairy roots of Plumbago indica

Abstract: Spontaneous shoot regeneration was observed from Agrobacterium rhizogenes-induced hairy roots of Plumbago indica when these were incubated in liquid MS medium for a period of 3 weeks under continuous light. Insertion of the rolB gene in putative transformed plants was confirmed by PCR and sequencing. Transformed plants grown for a period of 1 week on solid MS medium containing 0.5 mg l -1 6-benzyladenine and then transplanted to growth regulator-free medium showed better overall growth than control plants. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In our study no shoot induction was observed in the hormone-free medium which resembles the results of studies on Pogostemon cablin by He-Ping et al (2011). In contrast, spontaneous regeneration of transformed plants from hairy roots of Plumbago indica (Gangopadhyay et al 2010) and Centaurium erythraea (Subotic et al 2009) was reported. Mano and Matsuhashi (1995) reported that horseradish plants can easily induce adventitious shoots from hairy roots without the addition of plant growth regulators.…”
Section: Shoot Regeneration From Hairy Root Culturessupporting
confidence: 87%
“…In our study no shoot induction was observed in the hormone-free medium which resembles the results of studies on Pogostemon cablin by He-Ping et al (2011). In contrast, spontaneous regeneration of transformed plants from hairy roots of Plumbago indica (Gangopadhyay et al 2010) and Centaurium erythraea (Subotic et al 2009) was reported. Mano and Matsuhashi (1995) reported that horseradish plants can easily induce adventitious shoots from hairy roots without the addition of plant growth regulators.…”
Section: Shoot Regeneration From Hairy Root Culturessupporting
confidence: 87%
“…On the other hand, in our study, an addition of any plant growth regulators nor changing the culture conditions were not necessary for obtaining shoot regeneration from hairy roots. Spontaneous regeneration of shoots from hairy root cultures has been also reported earlier for, inter alia T. indica (Chaudhuri et al 2006), Centaurium erythraea (Piatczak and Wysokinska 2006), P. indica (Gangopadhyay et al 2010), Ophiorrhiza rugosa (Kamble et al 2011) and Rauwolfia serpentina (Mehrotra et al 2013). According to Mehrotra et al (2013) the depletion of nutrient contents during continuous growth and changes in levels or sensitivity to phytohormones in transformed tissues can be considered as factors responsible for the spontaneous regeneration of shoots.…”
Section: Discussionsupporting
confidence: 74%
“…Several differences were observed in the morphology and biomass of SD-and HR-R. glutinosa plants, most notably, a considerable increase in root biomass of the HR-plants. This is one of the most commonly observed properties of pRi-transformed regenerants, which was found also in such transgenic plants as Catharanthus roseus (Choi et al 2004), T. indica (Chaudhuri et al 2006), Aralia elata (Kang et al 2006) and P. indica (Gangopadhyay et al 2010). The increase is due to the influence of the introduced rol genes on hormonal synthesis and sensitivity.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Rapid growth, low doubling time, easy maintenance and the ability to synthesize a wide variety of chemical compounds, are some of the advantages that have made hairy roots as an important source for the production of secondary metabolites. Genetic transformation by Agrobacterium rhizogenes is an effective method to increase the accumulation of secondary metabolites in plant cells (Gangopadhyay et al 2010). A. rhizogenes is a gram-negative, soil bacterium.…”
Section: Introductionmentioning
confidence: 99%